Global Differences in Heart Failure With Preserved Ejection Fraction: The PARAGON-HF Trial - Tromp, Jasper; Claggett, Brian L; Liu, Jiankang; Jackson, Alice M; Jhund, Pardeep S; Køber, Lars; Widimský, Jiří; Boytsov, Sergey A; Chopra, Vijay K; Anand, Inder S; Ge, Junbo; Chen, Chen-Huan; et al. (Circulation. Heart failure, 2021)
BACKGROUND: Heart failure with preserved ejection fraction (HFpEF) is a global public health problem with important regional differences. We investigated these differences in the PARAGON-HF trial (Prospective Comparison of Angiotensin Receptor Neprilysin Inhibitor With Angiotensin Receptor Blocker Global Outcomes in HFpEF), the largest and most inclusive global HFpEF trial. METHODS: We studied differences in clinical characteristics, outcomes, and treatment effects of sacubitril/valsartan in 4796 patients with HFpEF from the PARAGON-HF trial, grouped according to geographic region. RESULTS: Regional differences in patient characteristics and comorbidities were observed: patients from Western Europe were oldest (mean 75±7 years) with the highest prevalence of atrial fibrillation/flutter (36%); Central/Eastern European patients were youngest (mean 71±8 years) with the highest prevalence of coronary artery disease (50%); North American patients had the highest prevalence of obesity (65%) and diabetes (49%); Latin American patients were younger (73±9 years) and had a high prevalence of obesity (53%); and Asia-Pacific patients had a high prevalence of diabetes (44%), despite a low prevalence of obesity (26%). Rates of the primary composite end point of total hospitalizations for HF and death from cardiovascular causes were lower in patients from Central Europe (9 per 100 patient-years) and highest in patients from North America (28 per 100 patient-years), which was primarily driven by a greater number of total hospitalizations for HF. The effect of treatment with sacubitril-valsartan was not modified by region (interaction P>0.05). CONCLUSIONS: Among patients with HFpEF recruited worldwide in PARAGON-HF, there were important regional differences in clinical characteristics and outcomes, which may have implications for the design of future clinical trials. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT01920711.
Keywords: Stroke Volume; aminobutyráty; Female; antagonisté receptorů pro angiotenzin; fixní kombinace léků; ženské pohlaví; Heart Failure; Global Health; celosvětové zdraví; kvalita života; lidé; srdeční selhání; dvojitá slepá metoda; neprilysin; hospitalizace; Valsartan; Risk Factors; Neprilysin; Double-Blind Method; Male; Aged; valsartan; Hospitalization; bifenylové sloučeniny; tepový objem; Aminobutyrates; rizikové faktory; senioři; mužské pohlaví; Angiotensin Receptor Antagonists; Biphenyl Compounds; Quality of Life; Drug Combinations; Humans